Evaluation of the blood neutrophil‐to‐lymphocyte ratio as a biomarker for meningoencephalitis of unknown etiology in dogs. (5th August 2022) - Park, Jooyoung; Lee, Dohee; Yun, Taesik; Koo, Yoonhoi; Chae, Yeon; Kim, Hakhyun; Yang, Mhan‐Pyo; Kang, Byeong‐Teck
Abstract: Background: The neutrophil‐to‐lymphocyte ratio (NLR) has been identified as a biomarker in several inflammatory and autoimmune diseases. Multiple sclerosis (MS) has been found to be associated with changes in the NLR in humans. Objectives: To examine the diagnostic value of the NLR in meningoencephalitis of unknown etiology (MUE) in dogs. Animals: Thirty‐eight MUE dogs, 20 hydrocephalic dogs, 10 brain tumor (BT) dogs, 32 idiopathic epilepsy (IE) dogs, and 41 healthy dogs. Methods: Retrospective study. Medical records were reviewed to identify dogs with a diagnosis of neurologic disease. The NLR was determined in all dogs. Results: The median NLR was significantly higher in MUE dogs (6.08) than in healthy (1.78, P < .001), IE (2.50, P < .05), and hydrocephalic dogs (1.79, P < .05). The area under the receiver operating characteristic curve of the NLR for differentiation between MUE and healthy dogs was 0.96, and between the MUE dogs and dogs with other forebrain diseases was 0.86. An optimal cutoff of 4.16 for the NLR had a sensitivity of 71.1% and specificity of 83.9% to differentiate the MUE dogs from the dogs with other forebrain diseases. Conclusions and Clinical Importance: The NLR could be a biomarker for diagnosing MUE and distinguishing it from other intracranial diseases in dogs.